Effects of Cimetidine and Phenobarbitone on Paracetamol Induced Hepatotoxic Rats (Bangladesh Journal of Physiology and Pharmacology, 2010)
The effects of cimetidine and phenobarbitone on paracetamol induced hepatotoxicity were studied in Long Evans Norwegian strain rats of either sexes. Orally administration of paracetamol 150 mg/ kg body weight for 21 days. On 22nd days after treatment there was significant increase of serum Alanine transaminase (AST), Aspartate transaminase (AST) and Alkaline phosphatase (Alk. phos) level. Orally administration of phenobarbitone 20 mg/kg b.w. along with paracetamol produced highly significant rise of serum ALT, AST and Alk. phos, levels as compared to the paracetamol treated group. But simultaneous administration of paracetamol and cimetidine produced significant decrease of serum ALT, AST and Alk. phos.level. When phenobarbitone is used concurrently with paracetamol, induced hepatic microsomal enzyme system which in turn aggravates the paracetamol induced hepatotoxicity but when cimetidine was administered simultaneously with paracetamol inhibited hepatic microsomal enzyme system and exhibits a protective role on paracetamol induced hepatotoxicity.The experiment was designed to demonstrate the effect of paracetamol on hepatotoxicity and its prevention by simultaneous administration of cimetidine. Further experiment was also designed to demonstrate the induction of hepatic microsomal enzyme system (HMES) by phenobarbitone on paracetamol induced hepatotoxicity. DOI: 10.3329/bjpp.v23i1.5725Bangladesh J Physiol Pharmacol 2007; 23(1&2) : 13-15